Effect of the solidification time on the median particle size of powders produced by water atomisation. (14th March 2016) - Pasupathy, M.; Martín, J. M.; Rivas, A.; Iturriza, I.; Castro, F.
Abstract : Present empirical correlations to predict the median particle size of water atomised powders have a validity restricted to a particular atomiser and alloy family. This work proposes a mathematical function that takes into account the influence of the heat transfer coefficient and, therefore, of the solidification time on the median particle size. This equation is applied in combination with previously proposed empirical correlations to extend their validity to a broader range of alloys. Experiments were conducted with alloys of different melting point (Fe base, Cu base and Sn). Quantitative measurements of the median particle size, tap density and several shape factors, and qualitative observations of the particle shape confirmed the importance of the heat transfer rate. It is shown that the inclusion of the solidification time effect results in a better agreement between calculated and experimental data when both low and high melting temperature alloys are taken together.